ZIONISME YAHUDI DAN TANTANGAN DAKWAH ISLAM - Muhammad Syarif Hasyim (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2012)
Before the birth of the state of Isreael, the Jewish nation was scattered in several countries, particularly in Europe and America. They are in a state of being suppressed, deprivated of political rights, suffering from expulsion and massacre. This condition encourages them to seek a unity. They communicate throuh promoting the issues of nationality and human rights. Thet communicate with the leaders of western countries. For internal consolidation, the Jews utilize religious slogans which they believe. From this emerge a movement called